Using Mind Mapping Presentation Videos Using Prezi in Learning English at MTsN 4 Pasaman - Yulia Oktarina (Yayasan Citra Dharma Cindekia, 2022)
This study aims to describe (1) the use of mind mapping video presentations using prezi in learning English , (2) the learning outcomes obtained by students using mind mapping presentation videos using prezi in learning English . This study uses a quantitative research design. The subjects of this study are class IX.2 MTsN 4 Pasaman students . The object of this research is the use of mind mapping video presentations using Prezi in learning English . The data collection method used is the method of observation, interviews, and documentation. The results of this study are the increase in the average level of student participation in learning English before the cycle is only 57% which consists of 7 indicators, namely attention by 60%, asking 54%, expressing opinions by 36%, understanding the material by 57%, solving problems by 60%, discipline by 70%.